New additions of three grass species to the flora of Nepal - Rajbhandari, Keshav R.; Dahal, Sajan (Journal of Plant Resources, 2008)
New additions of three grass species to the flora of Nepal are reported. They are Lolium multiflorum Lam., Orinus thoroldii (Stapf ex Hemsl.) Bor and Paspalum dilatatum Poir. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 17-18